Alan Davison. 24 March 1936 — 14 November 2015. (31st December 2017) - Green, Malcolm L. H.; Cummins, Christopher C.; Kronauge, James F.
Abstract : In 1958 Professor Alan Davison started his research career at an exciting time for the field of organometallic chemistry. New developments in spectroscopy, instrumentation and techniques to manipulate materials in controlled environments to avoid reaction with water or oxygen were becoming widely available. Controlling exposure of an element with highly reactive oxygen facilitated the isolation, characterization and discovery of an abundance of unknown compounds. Alan was an insightful and talented synthetic chemist and made many new and interesting organometallic compounds. He used the earliest commercial nuclear magnetic resonance instruments to characterize the then poorly understood transition metal hydrides and also to identify the earliest fluxional organometallic molecules. In 1970 he entered a collaboration with Professor Alun G. Jones, a nuclear chemist at Harvard Medical School, to characterize and develop the chemistry of technetium. They made a major discovery of technetium molecules which had the ability to selectively locate in human heart muscle, thereby vastly expanding the practice of nuclear medicine to a global community. Professor Alan Davison was also widely known for his outstanding qualities as a teacher and mentor.